Prediction of soft tissue coverage following distal femur bone sarcoma resection: A preliminary report - AKGÜLLE, AHMET HAMDİ; EROL, BÜLENT; BAYKAN, SAİD ERKAM (WILEY, 2022)
We aimed to examine the predictability of the need for soft tissue reconstruction during limb-sparing surgery through preoperative magnetic resonance (MR) imaging in patients diagnosed with a malignant bone tumor in the distal femur. The study included 42 patients who were operated for a bone sarcoma of the distal femur at our clinic between 2016 and 2018. The recorded parameters included the demographic characteristics of the patients, tumor diagnosis, tumor side, total tumor volume, tumor soft tissue component volume, tumor soft tissue component volume-to-total tumor volume ratio, tumor localization by MR imaging, the need for soft tissue reconstruction, the muscles used for soft tissue reconstruction, the biopsy site, and the biopsy type. Tumor volume was calculated on MR imaging of the distal femur region performed before surgery. Our study established cut-off values for soft tissue reconstruction need following resection as a total tumor volume of 96.4 cm(3), a tumor soft tissue component volume of 22 cm(3), a tumor soft tissue component volume-to-total tumor volume ratio of 48.9%, and tumor localization in two different regions on axial distal femoral MR images. Considering these cut-off values, by calculating tumor volume values preoperatively we can predict the need for rotational muscle flaps for soft tissue coverage following distal femur bone sarcoma resection and endoprosthesis reconstruction. Anticipating the need for soft tissue reconstruction may affect the duration and success of the operation.
Keywords: bone sarcoma; distal femur; soft tissue reconstruction